Effectiveness of First Aid Learning in Rural Areas: Local Language Short Film vs. “Toma Cemas” Module - Nastiti, Eky Madyaning; Darotin, Rida; Ekaprasetiya, Feri; Wulansari, Yunita Wahyu; Wirasakti, Guruh (Universitas Tribhuwana Tunggadewi, 2025)
Musculoskeletal injuries in school children are one of the problems found, especially in rural areas. Providing health education on first aid for musculoskeletal injuries can build knowledge, motivation, and self-efficacy, so it is important to develop new strategies. This study analyzes the comparative effect of local language first aid short film media and the